Analisis Bibliometrik Perkembangan Penelitian Inovasi Kebijakan di Indonesia - Hardiyanto Rahman (Research and Development Agency Ministry of Home Affairs, 2023)
Policy innovation in Indonesia is not only interpreted as digitalization, but also as the values of a policy (policy values). Related to the statement, this study aims to look at research trends related to policy innovation in Indonesia. This research uses bibliometric analysis and content analysis sourced from the Scopus database to be processed and analyzed from the topics and contents of the articles, as well as using the Vosviewer application to create bibliometric maps. This research reveals that the most publications were made in 2022 with 6 articles, and the most citations in 2017 with 81 out of 20 other articles with the title Perception across scales of governance and Indonesian peatland fires. For Co-Authorship, the authors are joined in 19 clusters with 20 state additions from Indonesia. It was also found that the most published policy innovations in Indonesia relate to digital and online economic technology innovation policies, natural resource policies and sustainable development, health policies, policies on transportation and public facilities, employment policies, economic policies, village financial management, tourism development. Meanwhile, Policy Innovations, which are the least frequently published, relate to science and technology governance, urban planning, environmental management, competition law and policy, So that the future is potentially for research and publication.